26. CASE STUDY ON THE INFLUENCE OF USTAZ HANAFI'S LEADERSHIP ON POLICIES AND PRACTICES IN PERSATUAN SENI SILAT CEKAK MALAYSIA (PSSCM) - Maoinser, Mohd Azuwan; Abdullah, Abdul Hazim; Mohd Zainudin, Anis Suria (Journal of Islamic, Social, Economics and Development, 2024)
Ustaz Hanafi founded Persatuan Seni Silat Cekak Malaysia (PSSCM) as a community-based, non-governmental organization (NGO) centered around the martial art of Silat Cekak. However, despite PSSCM's recognition as a reputable NGO in Malaysia, there is a lack of documented evidence showcasing Ustaz Hanafi's impact as its President in elevating Silat Cekak to this status. This study aims to scrutinize Ustaz Hanafi's role as the founder and first President of PSSCM, specifically in shaping the organization's policies and practices. The investigation employs interview-based research involving 15 active members directly taught by Ustaz Hanafi. The findings highlight Ustaz Hanafi's professionalism as a leader, evident in the establishment of a constitution and legal registration under the Malaysian Registry of Societies. Ustaz Hanafi introduced clothing policies tailored to different occasions, a rare practice within Silat associations of his time. Furthermore, he implemented economic sustainability policies, ensuring that both the headquarters and state branches possessed real estate assets. Ustaz Hanafi instilled good practices among PSSCM members, emphasizing the importance of keeping promises, maintaining trust, and avoiding falsehoods. Time punctuality was a focal point for him, demonstrating his commitment to discipline among PSSCM members. He integrated teaching, martial arts, and association as core administration elements to foster unity, successfully distinguishing personal and public interests. Respondents describe Ustaz Hanafi as an open-minded and transparent leader, willing to engage with individuals irrespective of their status or position. This study illuminates Ustaz Hanafi's crucial role in shaping PSSCM into an exemplary NGO, showcasing his professional leadership, innovative policies, and ethical practices while providing valuable insights for organizational development within Malaysia.